Trends in the epidemiology of oral squamous cell carcinoma in Western UP: An institutional study - Sharma Preeti; Saxena Susmita; Aggarwal Pooja (Wolters Kluwer Medknow Publications, 2010)
Objective: The purpose of the study was to identify trends in incidence rates of oral squamous cell carcinoma (OSCC) at specific anatomic sites or within specific age or sex groups in the Western Uttar Pradesh population. Materials and Methods: The study covers the period from January 2004 through April 2009. OSCC cases were retrospectively analysed for site, age, gender and habits and the findings were formulated to chart the trends in Western U.P. Results: The study revealed a male to female ratio of 2.2:1 with the largest number of OSCCs developing in the fourth and fifth decades of life. Overall, the most common site was the buccal mucosa (63.75%), followed by retromolar area (15%), floor of the mouth (11.25%), lateral border of the tongue (3.75%), labial mucosa (3.75%), and palate (2.5%). Smokeless tobacco habit was more prevalent than smoking tobacco in both men as well as women. Karl - Pearson′s correlation coefficient was calculated to find the degree of association between the two variables i.e. between gender to buccal mucosa and gender to smokeless and smoking tobacco habits, which were found to be positively correlated with respect to the age. Conclusion: Oral cancer is an important cause of morbidity and mortality worldwide with an incidence rate that varies widely by geographic location. Even within one geographic location, the incidence varies among groups categorized by age, sex, site or habit.